The Concept of Rational Emotif Behavior Therapy Approach in Building Self-Esteem for Slow Learner Children - Rischa Pramudia Trisnani; M. Ramli; Carolina Ligya Radjah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This article describes the concept of Rational Emotive Behavior Therapy in building Self- Esteem for slow learner children. The REBT concept helps clients learn to challenge irrational thinking and develop thinking habits in practical and rational ways. This shift allows the individual to have a more effectively and ultimately experience healthy emotions. Descriptive research including library research using comparative studies of systems or concepts. The concept used is the A-B-C-D-E-G model in building the Self Esteem of slow learner children. The stages of self-esteem formation with the concept of Rational Emotive Behavior Therapy change individual cognitive processes in the form of perception, meaning, judgment, and it plays an essential role in the development and maintaining emotions and behavioral responses. It reduces dissatisfaction with body image and unconditional self-acceptance; accepted beliefs or not being accepted is not something to regret because it is not terrible.